Understanding Ubl-Rpn1 Intermolecular Interaction - Pradhan, N.; Sharma, Kartik (Journal of Advanced Pharmaceutical Science And Technology, 2014)
ALS is the neurodegenerative disease which is caused due to breakdown in interaction between UBL and rpn1. In this study, we explore the interaction of UBL and rpn1 which is involved in protein degradation. Protein recycling system plays a crucial role in degradation of deformed or damaged proteins. Task of degradation of damaged ubiquitinated proteins is completed by proteasome with the help of ubiquilin2 protein which links 19s proteasome and poly-Ub chain attached to damaged protein. More specifically, N-terminal UBL domain interacts with rpn1 subunit of base complex of 19s proteasome and C-terminal UBA domain interacts with tetra poly-Ub chain attached to damaged protein. In present study, UBL domains are docked against homology modeled rpn1 with the help of Patch dock server. Further the docked structures are refined using fire dock server and best docked structure is chosen having global energy -16.71. Best docked structures are analyzed using swiss-pdb viewer software to show hydrogen bonds between interacting proteins. Here we explore a mutation E6A and P11A in UBL structure with the help of YASARA which is significantly increasing the interaction between interacting proteins in terms of hydrogen bonds.
Keywords: ALS; Ubiquilin2; Proteasome; tetra-Ub chain; docking studies- patch dock; fire dock; swiss-pdb viewer.